Pengaruh Strategi Belajar Reading Guide terhadap Daya Baca Siswa pada Mata Pelajaran Akidah Akhlak - Ahmad Fuadi; Muhammad Khalidin (Fakultas Syariah IAIN Laa Roiba Bogor, 2020)
This study examines three things, first; How is the implementation of the reading guide learning strategy for class VII with Akidah Akhlak subjects at MTs An-Nadia, Kwala Serapuh village, Langkat Regency. Second; How is the reading ability of class VII students in the Akidah Akhlak subject at MTs An-Nadia, Kwala Serapuh village, Langkat Regency. Third; Is there an effect of reading guide learning strategies on the reading power of seventh grade students in Akidah Akhlak subjects at MTs An-Nadia, Kwala Serapuh village, Langkat Regency. This study uses a quantitative method, by taking a sample of 17 students. While the questionnaire for each variable amounted to 12 questions, with product moment research analysis. The results of this study indicate that the implementation of the reading guide strategy for class VII students in the Akidah Akhlak subject at MTs An-Nadia, Kwala Serapuh village, Langkat Regency is in good classification, with the percentage of respondents' answers being 65.5%. The reading ability of class VII students in the Akidah Akhlak subject at MTs An-Nadia, Kwala Serapuh village, Langkat Regency is in the medium classification, with the percentage of respondents' answers being 62.25%. The application of the reading guide learning strategy has a positive effect on the reading power of seventh grade students in the Akidah Akhlak subject at MTs An-Nadia, Kwala Serapuh village, Langkat Regency with a low correlation of 0.258. To teachers of moral creed at MTs An-Nadia, Kwala Serapuh village, Langkat Regency, to carry out teacher duties more professionally by increasing creativity in teaching so that student learning achievement can be further improved, among others, by showing an increase in the use of learning strategies and student questions and answers in the learning process.